2019
DOI: 10.1002/jcp.28128
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA hsa_circRNA_101996 increases cervical cancer proliferation and invasion through activating TPX2 expression by restraining miR‐8075

Abstract: In recent years, circular RNAs have been shown to serve as essential regulators in several human cancers. Nevertheless, the function and mechanism of CircRNA in cervical cancer remain elusive. In the present study, we showed that hsa_circRNA_101996 was highly expressed in cervical cancer tissues compared with matched normal tissues by bioinformatics analysis. We showed that the expression level of hsa_circRNA_101996 in cervical cancer tissues was positively correlated with TNM stage, tumor size, and lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
117
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(121 citation statements)
references
References 33 publications
2
117
0
Order By: Relevance
“…20 Moreover, results from Xianchao Kong el al showed that circ101996 might act as an oncogene of CC through increasing the expression of TPX2 through miR-8075. 21 In this study, a circRNA microarray analysis was conducted on two CC-associated circRNA GSE datasets (GSE102686 and GSE113696) downloaded from the GEO database (www.ncbi.nlm.nih.gov/geo) to screen specific circRNAs that might involve in the pathogenesis of CC. Among the different expressed circRNAs, circ_103973 was identified to be significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…20 Moreover, results from Xianchao Kong el al showed that circ101996 might act as an oncogene of CC through increasing the expression of TPX2 through miR-8075. 21 In this study, a circRNA microarray analysis was conducted on two CC-associated circRNA GSE datasets (GSE102686 and GSE113696) downloaded from the GEO database (www.ncbi.nlm.nih.gov/geo) to screen specific circRNAs that might involve in the pathogenesis of CC. Among the different expressed circRNAs, circ_103973 was identified to be significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported the up-regulation and miRNA-sponging roles of circRNAs in CC. For instance, circ_101996 was overexpressed in cervical cancerous tissues [44]. One study showed that circ_0084927 was signi cantly up-regulated in malignant pleural effusion (MPE) of lung cancer [45].…”
Section: Discussionmentioning
confidence: 99%
“…Despite intense screening and various treatment options such as surgery, radiotherapy and chemotherapy, prognosis in CESC remains poor due to high risk of metastasis and recurrence. Additionally, mounting evidence suggests that altered expression of many genes contributes to CESC pathogenesis [15][16][17]. Therefore, we expect to identify some sensitive and novel biomarkers for diagnosis and prognosis in CESC.…”
Section: Discussionmentioning
confidence: 99%